Modelling of the extreme values of men`s triple jump and its related events and their correlations - Xu, M.; Zhou, B.; Wei, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Treating triple jump and its related events as a system, the present study explores the extreme values of these events and their correlation with special attributes. The study findings will attempt to provide some guidance for the special attribute training of future triple jumpers.